Potret Pemanfaatan Biochar dari Biomassa Lokal Sebagai Solusi Berkelanjutan di Sumatera Barat, Indonesia - Refita Mayasari (Publication of the International Journal and Academic Research, 2024)
The paper presents an extensive exploration of the utilization of biochar derived from indigenous biomass as a sustainable solution in West Sumatra, Indonesia. The region, abundant in diverse biomass resources, offers substantial prospects for the production and application of biochar. This paper aims to elucidate the accessible biomass reservoirs within the area, expound upon the biochar production process, and study its various applications in overcoming sustainability problems. A comprehensive assessment of existing literature and case studies is conducted to scrutinize the feasibility and impact of biochar application across multiple domains, notably in agriculture, waste management, and environmental conservation. Through this analysis, the study strives to uncover the potential benefits and challenges associated with integrating biochar technology into various facets of West Sumatra's landscape. Furthermore, the paper undertakes an evaluation of the environmental advantages and economic implications attributed to the adoption of biochar technology within the region. This evaluation encompasses discussions on the technology's capacity to curtail greenhouse gas emissions and enhance soil fertility, thereby contributing to the overall ecological balance and agricultural productivity. By identifying key challenges and opportunities, this study endeavors to furnish recommendations targeted at policymakers, stakeholders, and the local community. These recommendations aim to facilitate and encourage the widespread adoption of biochar as a sustainable solution in West Sumatra. Such adoption is envisioned as a pivotal step towards the preserving of the local environment while concurrently fostering socio-economic development within the region. Ultimately, the study seeks to underscore  the potential transformative impact of biochar  technology as a catalyst  for  environmental preservation and sustainable growth in West Sumatra, Indonesia.